Annulation of 2'‐Chlorochalcones and Elemental Sulfur toward the Synthesis of 2‐Aryl Thiochromenones. Issue 28 (22nd July 2022) - Huynh, Tan N.; Huynh, Tien V.; Ca, Thuy T.; Tran, Dat T.; Pham, Hai H.; Nguyen, Tung T.; Phan, Nam T. S.
Abstract: Herein we report a method for the synthesis of 2‐aryl thiochromenones via a sulfuration of 2'‐chlorochalcones. The chalcones could be prepared in advance or in situ obtained from 2'‐chloroacetophenones and aromatic aldehydes. The conditions were tolerant of functionalities including chloro, fluoro, methylthio, phenoxy, and trifluoromethyl groups. 2‐Heteroaryl thiochromenones could also be obtained in moderate yields. Our method appears to be a simple, general tactic to afford 2‐aryl thiochromenones from commercial starting materials. Abstract : Thiochromenones are valuable compounds that found uses in studies of medicinally relevant molecules. Herein we report a method for annulation of 2'‐chlorochalcones and elemental sulfur in the absence of transition metals. Many functionalities are well tolerant of reaction conditions.